A new donor cornea harvesting technique for posterior lamellar keratoplasty. Issue 9 (19th August 2005) - Suwan-apichon, O; Rizen, M; Reyes, J M G; Herretes, S; Behrens, A; Stark, W J; Chuck, R S
Abstract : Aims: To describe a technique for posterior lamellar keratoplasty donor preparation. Methods: In an experimental study eight human donor research corneas were mounted onto an artificial anterior chamber and deep stromal pockets dissected. Four corneas were mounted in the standard endothelial side down orientation and dissected using standard instruments (group 1). Another four corneas were mounted endothelial side up and dissected using a flat spatula (group 2). Trephined lamellar graft thickness was assessed by ultrasound pachymetry. The grafts were also analysed using vital staining of the endothelium and standard histological preparation. Results: Achieved posterior graft thickness was 118 (SD 32) μm (group 1) and 92 (23) μm (group 2) (p = 0.324). Percentage of devitalised endothelial cells was 0.86% (1.48%) (group 1) and 3.9% (2.9%) (group 2) (p = 0.185). The dissections using both harvesting techniques remained in plane and were smooth. Conclusions: A blunt spatula and endothelium side up orientation on an artificial anterior chamber can be used to create posterior lamellar dissections without compromising endothelial cell number or planarity when compared to standard endothelium side down harvest.